(untitled) (Research, Society and Development, 2020)
Objective: to investigate domestic violence as a cross - cutting theme in the professional training of undergraduate health courses. Method: qualitative study of the descriptive-exploratory type, carried out with 32 undergraduate students in nursing, dentistry, physiotherapy and medicine. We used the semi-structured interview for data collection and for data analysis the content analysis technique. Results: Domestic violence is being addressed in undergraduate courses in the health area restricted to some disciplines, not taking into account the complexity of the problem and facing future professionals to people in situations of domestic violence. Conclusion: domestic violence needs to be discussed during the professional training in a transversal way, and it is necessary to include the theme in the curricula for theoretical-practical articulation, including the construction of learning and development of skills and abilities that can subsidize professional practice.